Continuous quality improvement program and its results of Korean Society for Cytopathology - Yoo-Duk Choi; Hoon-Kyu Oh; Su-Jin Kim; Kyung-Hee Kim; Yun-Kyung Lee; Bo-Sung Kim; Eun-Jeong Jang; Yoon-Jung Choi; Eun-Kyung Han; Dong-Hoon Kim; Younghee Choi; Chan-Kwon Jung; et al. (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Since 1995, the Korean Society for Cytopathology has overseen the Continuous Quality Improvement program for cytopathology laboratories. The Committee of Quality Improvement has carried out an annual survey of cytology data for each laboratory and set standards for proficiency tests. Methods Evaluations were conducted four times per year from 2008 to 2018 and comprised statistics regarding cytology diagnoses of previous years, proficiency tests using cytology slides provided by the committee, assessment of adequacy of gynecology (GYN) cytology slides, and submission of cytology slides for proficiency tests. Results A total of 206 institutes participated in 2017, and the results were as follows. The number of cytology tests increased from year to year. The ratio of liquid-based cytology in GYN gradually decreased, as most of the GYN cytology had been performed at commercial laboratories. The distribution of GYN diagnoses demonstrated nearly 3.0% as atypical squamous cells. The rate for squamous cell carcinoma was less than 0.02%. The atypical squamous cell/squamous intraepithelial lesion ratio was about 3:1 and showed an upward trend. The major discordant rate of cytology-histology in GYN cytology was less than 1%. The proficiency test maintained a major discordant rate less than 2%. The rate of inappropriate specimens for GYN cytology slides gradually decreased. Conclusions The Continuous Quality Improvement program should be included in quality assurance programs. Moreover, these data can contribute to development of national cancer examination guidelines and facilitate cancer prevention and treatment.